Sistem Akuntansi Penerimaan Kas Pada Penjualan Expedisi PT. Bulan Cahaya Angkasa Medan - Cindy Fenita; Suriana Suriana; Widia Wardani (Departement of Mathematics Education, 2024)
The purpose of this research is to determine the accounting system for cash receipts from the sale of PT expedition services. Bulan Cahaya Angkasa Medan is running effectively and efficiently. To collect data, the author used field research techniques, namely through interviews with leaders, employees, observation and documentation. Meanwhile, research literature was obtained from literature and books related to the research carried out, for the data analysis technique the author used descriptive qualitative. This research was conducted at PT. Bulan Cahaya Angkasa Medan is located on Jalan Asia no 266 H Simpang Suasa Medan. Based on the results of the research and discussions that have been carried out, it is concluded that the accounting system for cash receipts from the sale of PT expedition services. Bulan Cahaya Angkasa Medan is quite good and functioning even though it still uses a manual system. The cash receipt system implemented by the company is mostly appropriate and effective because it is in accordance with theory so that it can support the cash receipt system well